2015
DOI: 10.4238/2015.october.19.23
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR evaluation of cell-free DNA subjected to various storage and shipping conditions

Abstract: ABSTRACT. In this study, we attempted to explore the factors affecting the yield of cell-free fetal DNA (cffDNA) obtained from maternal blood samples, including the use of different types of collection tubes, the interval between sample processing, and sample shipping under extreme weather conditions. Blood samples were drawn into K 3 EDTA tubes and cellstabilizing tubes (Streck blood collection tube, BCT) from women pregnant with male fetuses. Real time PCR was used to amplify a β-actin gene fragment to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Within this time interval we saw no correlation between shipping time and FF (Supplemental Fig. 3), confirming previous reports [2] and fitting within manufacturer guidelines (up to 14 days at 6-37°C) when using Streck tubes.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Within this time interval we saw no correlation between shipping time and FF (Supplemental Fig. 3), confirming previous reports [2] and fitting within manufacturer guidelines (up to 14 days at 6-37°C) when using Streck tubes.…”
Section: Resultssupporting
confidence: 89%
“…Indeed, some laboratories may not be checking FF or using optimal methods for detection that could potentially provide false-negative results to patients [1]. Technical factors that can influence FF and its estimation are sample handling [2] and the choice of bioinformatics tools (reviewed in [3]) [4]. Multiple biological factors have been identified that affect FF, including gestational age [4][5][6][7][8][9], weight and/or body mass index (BMI) [6][7][8][9][10][11][12], trisomies [7,[10][11][12][13], fetal crown-rump length [6,10,12], serum pregnancy-associated plasma protein-A [6,10,12], serum free β-human chorionic gonadotropin [6,10,12], hypertension [7], twins [7], smoking [10], and assisted conception [8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma samples are preferable to serum because release of DNA from leukocytes following collection can falsely increase measured concentrations 29–31. Other factors that may affect cfDNA concentrations are time between collection and processing,4 32 centrifugation methods,29 and storage conditions 29 33…”
Section: Introductionmentioning
confidence: 99%
“…Streck, Inc. (Omaha, NE, USA) developed blood collection tubes (Cell-Free DNA BCT ® ) which contain a formalin-releasing reagent leading to a slow fixation of the DNA and the cells in a blood sample. These collection tubes allow for storage of blood samples for several days at ambient temperature before starting the plasma preparation procedure [35][36][37][38][39]. While this would dramatically facilitate the sample logistic needed for a centralized high-throughput testing of methylated ccfDNA, these tubes are still expensive and a cost-driving factor in the overall complex procedure.…”
Section: Samplingmentioning
confidence: 99%